2011
DOI: 10.1002/jcb.23330
|View full text |Cite
|
Sign up to set email alerts
|

LPS induces phosphorylation of actin‐regulatory proteins leading to actin reassembly and macrophage motility

Abstract: Upon bacterial infection lipopolysaccharide (LPS) induces migration of monocytes/macrophages to the invaded region and production of pro-inflammatory mediators. We examined mechanisms of LPS-stimulated motility and found that LPS at 100 ng/ml induced rapid elongation and ruffling of macrophage-like J774 cells. A wound-healing assay revealed that LPS also activated directed cell movement that was followed by TNF-α production. The CD14 and TLR4 receptors of LPS translocated to the leading lamella of polarized ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
1
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(51 citation statements)
references
References 53 publications
1
47
1
2
Order By: Relevance
“…Earlier studies have demonstrated that LPS enhanced paxillin tyrosine phosphorylation in macrophages and bovine pulmonary arterial endothelial cells (7,19); however, the role of tyrosine phosphorylation of paxillin on LPS-induced endothelial barrier function is not well defined. We determined whether LPS modulates paxillin tyrosine phosphorylation in HLMVECs.…”
Section: Lps Stimulates Paxillin Tyrosine Phosphorylation In Hlmvecsmentioning
confidence: 96%
See 1 more Smart Citation
“…Earlier studies have demonstrated that LPS enhanced paxillin tyrosine phosphorylation in macrophages and bovine pulmonary arterial endothelial cells (7,19); however, the role of tyrosine phosphorylation of paxillin on LPS-induced endothelial barrier function is not well defined. We determined whether LPS modulates paxillin tyrosine phosphorylation in HLMVECs.…”
Section: Lps Stimulates Paxillin Tyrosine Phosphorylation In Hlmvecsmentioning
confidence: 96%
“…Paxillin has been shown to differentially regulate endothelial barrier function by growth factors via modulation of Rac-Rho signaling (4). Recent studies showed that LPS treatment is known to induce phosphorylation of paxillin in macrophages (19) and bovine pulmonary arterial ECs (7); however, little is known about the potential role of tyrosine phosphorylation of paxillin in regulating LPS-induced endothelial barrier dysfunction.…”
mentioning
confidence: 99%
“…Lipopolysaccharide (LPS), which is a bacterially derived endotoxin used as a positive proinflammatory control, promoted adhesion and spreading of cells, inducing the typical morphology of immune-activated macrophages (arrows). 30 In contrast, exposure to citrate AuNP, the NH 2 PVA polymer or NH 2 PVA-AuNP did not induce any change in morphology, with cells remaining small and round. Some material aggregates (arrows) were seen with NH 2 PVA polymer exposure.…”
Section: Impact Of Np On Macrophage Viabilitymentioning
confidence: 86%
“…It is considered to be possible that glucocorticoid contributes to the macrophage migration during the process of skeletal muscle repair after acute exercise. On the other hand, lipopolysaccharide (LPS), which strongly induces the differentiation into inflammatory macrophages, also affects the macrophage motility (Kleveta et al, 2012). A recent study indicated that a phenotype switch was not observed in CCR2 deficient mice (Lumeng et al, 2007), suggesting that the MCP1/CCR2 pathway likely contributes to macrophage polarization.…”
Section: Introductionmentioning
confidence: 98%
“…Nevertheless, the exact cellular and biological events that cause this macrophage migration toward injured muscle are not completely understood. The evaluations of macrophage infiltration have mainly consisted of two strategies: the immunohistochemical evaluations (examining macrophage accumulation in tissue) (Shireman et al, 2006;Kleveta et al, 2012), and the evaluation of chemotaxis by the Boyden chamber assay (Boyden, 1962) or a modified assay. Both of these made it difficult or impossible to evaluate the speed and direction of horizontal movement of the macrophages toward damaged muscle.…”
Section: Introductionmentioning
confidence: 99%